Bildmittenübersicht/Index Map 1:500 000 Heimefrontfjella SS 28-30/W, Antarktisexpedition 1985/86 - Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie); Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1987)
Flight index map of vertical aerial photography, 1985/86 expedition; Photographic material, Aerial photo scale and Flight dates, see map legend; Inset maps: Location diagram, Index to adjoining sheets; Scale: 1:500000; Projection: Lambert Conformal Conic; Bounding Box: POLYGON ((-18 -74, -9 -74, -9 -76, -18 -76, -18 -74))